2013
DOI: 10.1016/j.jhep.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

HCV NS5A and IRF9 compete for CypA binding

Abstract: Background Cyclophilin A (CypA) is vital for HCV replication. Cyp inhibitors successfully decrease viral loads in HCV-infected patients. However, their mechanisms of action remain unknown. Since interferon (IFN) can also suppress HCV replication, we asked whether a link between CypA and the IFN response exists. Methods We used cellular and recombinant pulldown approaches to investigate the possibility of a specific association of CypA with host ligands. Results We found for the first time that CypA binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…The N terminus of IRF9 is the DNA-binding domain, which is characterized by 5 tryptophan repeats and is highly conserved within the IRF family. 30 The pro-domain corresponds to a linker region, 13,40 which is reported to be the PPARα-binding domain. 13 Only the TAD of myocardin contributes to the association with IRF9.…”
Section: Discussionmentioning
confidence: 99%
“…The N terminus of IRF9 is the DNA-binding domain, which is characterized by 5 tryptophan repeats and is highly conserved within the IRF family. 30 The pro-domain corresponds to a linker region, 13,40 which is reported to be the PPARα-binding domain. 13 Only the TAD of myocardin contributes to the association with IRF9.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that NS5A possesses the ability to counteract the innate response to permit establishment of HCV replication 47. A very recent study demonstrated that cyclophilin A binds both NS5A and the IFN-regulatory factors, especially IRF9, and that alisporivir blocks all these interactions 48. Thus, one can envisage that contact between cyclophilin A and NS5A and/or specific IFN-regulatory factors modulates the innate response.…”
Section: Mechanism Of Action Of Alisporivirmentioning
confidence: 99%
“…These results demonstrated that CyPA indeed plays an additional role at the assembly step of HCV life cycle. A recent report showed that CyPA could also interact with the interferon (IFN) regulatory factor 9 (IRF9) [108] in vitro . However, because previous studies have demonstrated that CsA functions through an IFN-independent mechanism [95,99], the significance of the CyPA-IRF9 interaction remains unclear.…”
Section: Cyclophilins and Hcvmentioning
confidence: 99%